Relationship between perceived body image and body mass index in college students (Revista horizonte, 2015)
This study aimed to determine the relationship between perceived body image and the actual values of body mass index (BMI). 7 anatomical models for both sexes should choose according to their own body image was used. The BMI is calculated from the measurement of body weight and height, then the actual BMI with the BMI perceived compared. The sample was 47 college students (30 men and 17 women) aged between 19 and 20 years. The actual prevalence of normal weight BMI was 70% in men and 64.7% women. 26.7% of men and 5.9% of women selected models that correspond to their actual BMI, with men who see themselves better. The difference between perceived and actual BMI with the Student ofÂ ï´Â test was p = 0.002 and p = 0.385 for women and men. The degree of concordance with Cohen Kappa test was 0,265 for men and 0,043 for women. The difference in perception of body image by sex obtained a chi-square = 13.52 and p value = 0.001. Women tend to overestimate their body weight perceiving themselves fatter than they are, unlike men who tend to underestimate their weight perceiving themselves thinner. In both cases a distortion between perceived body image and body mass index (BMI) was observed.